Ca2+ entry via TRPC1 is essential for cellular differentiation and modulates secretion via the SNARE complex - Schaar, Anne (2019)
Fil: Schaar, Anne. University of North Dakota. School of Medicine and Health Sciences. Department of Biomedical Science; Estados Unidos